Pengaruh Teknik Pernapasan Buteyko Terhadap Pola Napas Tidak Efektif Pada Klien Asma Bronkial - Shinta Ramadhona; Wasisto Utomo; Yulia Rizka (Jurnal Vokasi Keperawatan (JVK), 2023)
Bronchial asthma is a medical condition that causes the airways of the lungs to swell and narrow. Due to swelling, the airways will produce excessive mucus, making it difficult to breathe and will cause coughing, shortness of breath, and wheezing. As for non-pharmacological therapies that can be used to reduce asthma recurrence and minimize the use of drugs, one of them is the Buteyko breathing technique. The Buteyko breathing technique can reduce the frequency of bronchial asthma attacks, prevent the severity of asthma and improve the Peak Expiratory Flow Rate (PEFR). Quasi experiment quantitative research design. The research sample was 34 respondents, the sampling technique was purposive sampling which was divided into 2 groups, namely 17 experimental respondents and 15 control group respondents. The measuring instrument used is an observation sheet for ineffective breathing patterns pre-test and post-test for 4 times in 2 weeks. The statistical test used is the Wilcoxon test and the Mann Whitney test. Buteyko's breathing technique has an effect on breathing patterns in bronchial asthma patients with value of dyspnea of ​​0.033< ɑ (0.05) and p value of breath frequency 0.001< ɑ (0.05). The Buteyko breathing technique can improve breathing patterns in people with bronchial asthma. These results are expected to be an alternative treatment to improve ineffective breathing patterns in bronchial asthma patients.